1998
DOI: 10.1002/srin.199805572
|View full text |Cite
|
Sign up to set email alerts
|

Burden distribution estimation in the blast furnace from stockrod and probe signals

Abstract: The burden distribution in the blast furnace is estimated on the basis of measurements provided by the stockrods in combination with information about changes in the gas temperatures measured by an above‐burden probe after each dump of burden. The former measurements yield an estimate of the local layer thickness close to the wall while the latter ones are used to evaluate the layer thickness in the center of the furnace. The layer thickness values estimated by the method and values computed on the basis of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Another reason is that the signals should be available at short sampling time, and such high-frequency data are seldom interesting in the analysis of the blast furnace process because of its inertia. In the present work 15) it was found that the stockrod signals should be sampled at least every two seconds in order to be able to provide accurate and useful information, especially in abnormal situations (such as slips).…”
Section: )mentioning
confidence: 98%
“…Another reason is that the signals should be available at short sampling time, and such high-frequency data are seldom interesting in the analysis of the blast furnace process because of its inertia. In the present work 15) it was found that the stockrod signals should be sampled at least every two seconds in order to be able to provide accurate and useful information, especially in abnormal situations (such as slips).…”
Section: )mentioning
confidence: 98%
“…There are basically only two regions where information can be obtained from inside the BF—the burden fill level at the top of the BF and the visual information of the raceway areas through the tuyere inspection windows. Information about the burden height can be derived from pointwise measurements via mechanical stockrod probes or microwave sensors, [ 12 ] 3D radar systems, [ 13,14 ] or, more recently, also the 3D reconstruction of the burden from optical sensors. [ 15,16 ] If the burden measurement system has a sufficient time resolution also the downward movement of the burden can be tracked.…”
Section: Introductionmentioning
confidence: 99%
“…To gain a better understanding of the gas distribution, horizontal or inclined probes have been applied above or below the burden surface. [3,11,12] These typically measure the temperatures and sometimes take gas samples to determine the gas composition at a number of discrete points along one radius. The in-burden probes also sample gas, while the above-burden probes usually only measure temperatures.…”
Section: Introductionmentioning
confidence: 99%